Dielectric Relaxation of Binary Mixtures of Diethylene Triamine + 2-Ethoxy ethanol in 1,4-Dioxane from Microwave Absorption Studies - Nimkar, M.J.; Pande, Rekha; Kalamse, G.M. (Asian Journal of Chemistry, 2016)
Single frequency concentration variational method of Gopal Krishna has been used to obtain dielectric relaxation time (t) and dipole moment (μ) for dilute solutions of binary mixtures of diethylene triamine and 2-ethoxy ethanol in 1,4-dioxane at different temperatures (22–50°C). Energy parameters (DH, DF, DS) for dielectric relaxation process of diethylene triamine + 2-ethoxy ethanol mixture containing 0, 37, 57, 78 and 100% diethylene triamine have also been calculated. Comparison has been made with corresponding energy parameters for viscous flow. Debye’s factor (C), Kalman’s factor (C') and excess inverse relaxation time were computed. The variation of relaxation time and excess relaxation time with weight fraction of diethylene triamine in the mixture confirms the solute-solute and solute-solvent interactions.